2017
DOI: 10.1093/europace/eux094
|View full text |Cite
|
Sign up to set email alerts
|

Cause-of-death analysis in patients with cardiac resynchronization therapy with or without a defibrillator: a systematic review and proportional meta-analysis

Abstract: Background: The additional benefit of a defibrillator in cardiac resynchronization therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Partly in line with our results, a recent meta-analysis of Barra et al [28], which included 18,874 patients from 44 studies and, demonstrated that CRT-D recipients were more often male, were younger, had less severe symptoms, less often experienced atrial fibrillation, were more often diagnosed with ischaemic heart disease, and more often received b-blocker therapy compared to CRT-P patients. The mortality rate was approximately twofold higher in CRT-P recipients, while sudden cardiac death was more prevalent in men, patients with ischaemic cardiomyopathy, and patients with severe HF symptoms (≥ NYHA class III).…”
Section: The Decision Between Crt-p Vs Crt-dsupporting
confidence: 91%
“…Partly in line with our results, a recent meta-analysis of Barra et al [28], which included 18,874 patients from 44 studies and, demonstrated that CRT-D recipients were more often male, were younger, had less severe symptoms, less often experienced atrial fibrillation, were more often diagnosed with ischaemic heart disease, and more often received b-blocker therapy compared to CRT-P patients. The mortality rate was approximately twofold higher in CRT-P recipients, while sudden cardiac death was more prevalent in men, patients with ischaemic cardiomyopathy, and patients with severe HF symptoms (≥ NYHA class III).…”
Section: The Decision Between Crt-p Vs Crt-dsupporting
confidence: 91%
“…Responders, especially superresponders to CRT, are at relatively lower risk of long-term cardiac mortality (3). Whether the primary prevention implantable cardioverter-defibrillator (ICD) improves outcomes over and above CRT is a matter of ongoing debate (4)(5)(6)(7), with the recent CeRtiTuDe cohort study revealing that the majority of the excess mortality among CRT-Pacemaker (CRT-P) subjects at 2-year follow-up is related to an increase in non-SCD (8).…”
Section: Introductionmentioning
confidence: 99%
“…We chose the analysis of Woods et al [12] because they were the only ones who performed a network meta-analysis of RCTs with individual patient data of CRT-D, CRT-P, OMT and ICD trials. More recent meta-analyses such as Barra et al [13] have not included other relevant RCTs. Input parameters for the transition probabilities and device longevity calculations are based on single RCTs used by six meta-analyses [11][12][13][22][23][24].…”
Section: Model Parametersmentioning
confidence: 99%
“…More recent meta-analyses such as Barra et al [13] have not included other relevant RCTs. Input parameters for the transition probabilities and device longevity calculations are based on single RCTs used by six meta-analyses [11][12][13][22][23][24]. Two additional references [9,25] were found by literature search via Pub-Med.…”
Section: Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation